1986
DOI: 10.1073/pnas.83.21.8268
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen-dependent mutagenesis in Escherichia coli lacking superoxide dismutase.

Abstract: Escherichia coil double mutants (sodA sodB) completely lacking superoxide dismutase (SOD) have greatly enhanced mutation rates during aerobic growth. Single mutants lacking manganese SOD (MnSOD) but possessing iron SOD (FeSOD) have a smaller increase, and single mutants lacking FeSOD but possessing MnSOD do not show such an increase. The enhancement of mutagenesis is completely dependent on the presence of oxygen, and treatments that increase the flux of superoxide radicals produce even higher levels of mutage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
160
1
1

Year Published

1987
1987
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 277 publications
(169 citation statements)
references
References 47 publications
7
160
1
1
Order By: Relevance
“…cerevisiae and E. coli SOD mutants are more prone to mutations (Farr et al, 1986;Huang et al, 2003) and contain high levels of intracellular free iron, which is evidenced by their marked Fenton-dependent DNA damage (Srinivasan et al, 2000). Consistent with these observations, we showed that SOD mutants of C. glabrata exhibited not only high levels of O 2 $2 , but also sensitivity to DNA damage agents and a high mutation rate (Fig.…”
Section: Deletion Of Sods Causes Accumulation Of Osupporting
confidence: 75%
See 1 more Smart Citation
“…cerevisiae and E. coli SOD mutants are more prone to mutations (Farr et al, 1986;Huang et al, 2003) and contain high levels of intracellular free iron, which is evidenced by their marked Fenton-dependent DNA damage (Srinivasan et al, 2000). Consistent with these observations, we showed that SOD mutants of C. glabrata exhibited not only high levels of O 2 $2 , but also sensitivity to DNA damage agents and a high mutation rate (Fig.…”
Section: Deletion Of Sods Causes Accumulation Of Osupporting
confidence: 75%
“…The protective role of the SODs in Candida glabrata been shown that mutations in SOD genes lead to increased rates of spontaneous mutation in E. coli (Farr et al, 1986) and Sac. cerevisiae (Gralla & Valentine, 1991).…”
Section: Deletion Of Sods Causes Accumulation Of Omentioning
confidence: 99%
“…The presence of SODs in virtually all facultative and aerobic organisms and several anaerobes suggests that O N{ 2 presents a problem for organisms growing in the presence of O 2 . Although in vitro experiments have established that O N{ 2 does not react detectably with biomolecules (Imlay, 2002(Imlay, , 2003, characterization of mutants lacking cytosolic SOD has provided the first in vivo evidence that excess O N{ 2 causes DNA damage (Farr et al, 1986;Keyer et al, 1995). Several studies conducted with Escherichia coli have provided strong support for the theory that O N{ 2 triggers the Fenton reaction (H 2 O 2 zFe 2z ?O N{ 2 zFe 3z zOH { ) by the oxidative release of iron from iron-containing molecules, such as those containing [4Fe-4S] clusters, thereby increasing the pool of free iron available to catalyse hydroxyl Abbreviations: Cm, chloramphenicol; DAPE, diaminopimelate epimerase; Em, erythromycin; MnSOD, manganese-containing superoxide dismutase; RACE-PCR, rapid amplification of cDNA ends PCR; ROS, reactive oxygen species; SOD, superoxide dismutase; tBOOH, tertbutylhydroperoxide.…”
Section: Reactive Oxygen Species (Ros) Including Superoxide Anion (O N{mentioning
confidence: 98%
“…Both sets of mutants exhibit catabolic and biosynthetic defects that stem from the inactivation of a family of dehydratases (15,16 (17,18). H 2 O 2 directly oxidizes unincorporated intracellular ferrous iron, some of which is associated with DNA (19,20):…”
Section: What Biomolecules Do Superoxide and H 2 O 2 Damage?mentioning
confidence: 99%